A Framework of Implementing Strategies for Active Student Engagement in Remote/Online Teaching and Learning during the COVID-19 Pandemic - Razzaqul Ahshan (MDPI AG, 2021)
The COVID-19 pandemic has caused a drastic shift of face-to-face teaching and learning to remote/online teaching and learning at all levels of education worldwide. Active student engagement is always a challenging task for educators regardless of the teaching modalities. The degree of challenge for active student engagement increases significantly in remote/online teaching and learning. This paper presents a framework that implements activities/strategies to ensure active student engagement in remote/online teaching and learning during this COVID-19 pandemic. The structure of the developed framework combines the balanced use of adjusted teaching pedagogy, educational technologies, and an e-learning management system. Teaching pedagogy involves various active learning techniques, synchronous teaching, asynchronous teaching, and segmentation. The educational technologies, such as Google Meet, Jamboard, Google Chat, Breakout room, Mentimeter, Moodle, electronic writing devices, etc., enable the developed framework for active student engagement. An e-learning management system, Moodle, is used for course management purposes. Over the last three semesters (Fall 2020, Spring 2021, and Summer 2021), the framework is tested for three different engineering courses. A questionnaire draws out student perception on the developed framework in terms of active student engagement that ensures student-student interactions, student-instructor interactions, social presence, reinforces learning and deepens understanding of the materials in remote teaching. The feedback also indicates that combining the utilized technologies, synchronous teaching, and active learning activities in the developed framework is effective for interactive learning; hence a practical approach for active student engagement in remote/online teaching and learning. The article focuses on contributing to present research and infusing future research direction about technology-enhanced active student engagement in Engineering Education.